Professional ethics: its foundations and practices - Hashi, Abdurezak Abdulahi (IIUM Press, 2018)
This book, Professional Ethics: Its Foundations and Practices uses comparative and analytical methods, and addresses the foundations, principles and approaches of ethics in relation to professional practices. Besides highlighting the meaning and concepts of moral ideals, this book also illustrates moral philosophies of leading conventional moral theories like moral egoism, altruism, utilitarianism, relativism, deontology and virtues theories of ethics, as well as moral concepts of major religious thoughts including Hinduism, Buddhism, Judaism, Christianity and Islam. With somewhat detailed explanations, this work offers a descriptive account on the genesis, the scope, the foundations, principles, virtues and milestones of the Islamic moral system. The scope and the components of professional ethics both from conventional and Islamic perspectives are then comparatively elucidated in the relevant chapters of this book. Additionally, it presents abridged explanations of the principles of applied ethics, its themes and practices in the given professional fields such as business, administration, engineering, politics, medicine and bioethics. This work does not however present meta-ethical analysis of the meaning and concepts of ethics, nor does it aim to present a normative account of morality. Rather this work seeks to understand applications of theoretical and formal ethics in real problematic issues to solve actual dilemmas in given professions.